2014
DOI: 10.1038/nature13381
|View full text |Cite
|
Sign up to set email alerts
|

Nanotwinned diamond with unprecedented hardness and stability

Abstract: Although diamond is the hardest material for cutting tools, poor thermal stability has limited its applications, especially at high temperatures. Simultaneous improvement of the hardness and thermal stability of diamond has long been desirable. According to the Hall-Petch effect, the hardness of diamond can be enhanced by nanostructuring (by means of nanograined and nanotwinned microstructures), as shown in previous studies. However, for well-sintered nanograined diamonds, the grain sizes are technically limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
402
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 667 publications
(470 citation statements)
references
References 28 publications
12
402
0
4
Order By: Relevance
“…These materials may be empirically related to high bulk modulus [651] and high shear modulus [600]. Strengthening due to grain size and nanotwinned structures also contributes to super hardness [652,653], resulting in hardness higher than that of single-crystal diamond [653].…”
Section: Superhard Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…These materials may be empirically related to high bulk modulus [651] and high shear modulus [600]. Strengthening due to grain size and nanotwinned structures also contributes to super hardness [652,653], resulting in hardness higher than that of single-crystal diamond [653].…”
Section: Superhard Materialsmentioning
confidence: 99%
“…The major types of superhard materials are the B-C-N-O compounds with characteristics of short and strong 3D covalent bonds. Diamond, the hardest known substance until recently [653], is a well-known carbon form that can be synthesized from graphite at HP conditions [660]. When graphite is compressed under ambient temperature, x-ray IXS experiments showed that it undergoes a 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 transition at 17 GPa, where half of the π-bonds between graphite layers convert to σ-bonds, whereas the other half remain as π-bonds in the HP form [72].…”
Section: Superhard Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ultrafine-grained Cu with nanoscale twins embedded in individual grains leads to a superstrength relative to conventional coarsegrained polycrystalline Cu [22]. In addition, nanotwins in ceramics have been found to dramatically enhance the hardness of diamond and boron nitride [23,24]. However, the influence of nanotwins on the mechanical properties of TE semiconductors remains largely unexplored.…”
mentioning
confidence: 99%
“…They recently made the astonishing discoveries that pressure could transform elemental sodium from a free-electron gas metal to a transparent insulator 5 , and that pressure could crush C 60 cages to form a new type of material with long-range ordering of short-range, disordered carbon clusters 6 . Meanwhile, researchers at Yanshan University made breakthroughs in the high-pressure synthesis of ultrahard nanotwinned cubic boron nitride 7 and nanotwinned diamond 8 , and researchers at Zhejiang University reported pressure-induced devitrification of Ce 3 Ala seemingly disordered metallic glass -to a single crystal 9 .…”
Section: Focus | Featurementioning
confidence: 99%